MODERN ASPECTS OF DIAGNOSIS AND PREDICTION OF THE UNFAVORABLE COURSE OF CORONARY ATHEROSCLEROSIS - Usmanova Yayraxon Gulamovna (Scholars Digest Publishing, 2023)
The article discusses the methodological aspects and diagnostic capabilities of modern radionuclide, tomographic and ultrasound research methods in the verification of coronary atherosclerosis
Keywords: atherosclerosis of the coronary arteries, myocardial perfusion scintigraphy, magnetic resonance and electron beam tomography, tissue Doppler imaging of the myocardium, through esophageal and transthoracic Doppler ultrasound of the coronary arteries